MicroRNA124-IL6R Mediates the Effect of Nicotine in Inflammatory Bowel Disease by Shifting Th1/Th2 Balance Toward Th1 - Qin, Zhen; Wang, Peng-Yuan; Wan, Jing-Jing; Zhang, Yu; Wei, Jie; Sun, Yang; Liu, Xia (Frontiers in Immunology, 2020)
Although it is generally believed that smoking protects against Th2-type ulcerative colitis (UC) and worsens Th1-type Crohn's disease (CD), the mechanism remains elusive. Nicotine is the main component of bidirectional regulation of tobacco on inflammatory bowel diseases (IBDs). Our previous studies have revealed that nicotine specifically elevates miR-124 level and protects against DSS colitis (resembling UC), while others reported that miR-124 is also highly expressed in CD, but it worsens CD. We speculate that miR-124 might mediate the dual role of nicotine in IBD by regulating Th1/Th2 balance. Results showed that miR-124 overexpression protected DSS-induced colitis with a Th1 polarization in murine peripheral blood lymphocytes and colon tissues, while miR-124 knockdown showed opposite effect. Similar results were obtained in human peripheral blood lymphocytes. Furthermore, miR-124 knockdown could abolish Th1 polarization effect of nicotine on DSS mice and human peripheral blood lymphocytes. IL-6R interference could significantly attenuate the role of miR-124 in Th1 polarization, indicating it is a downstream target of miR-124 on Th1/Th2 balance. Collectively, these data indicate that nicotine shifts Th1/Th2 balance toward Th1 through miR-124-IL-6R pathway, which might be responsible for its dual role in IBD.